Progressive 3D Printing Technology and Its Application in Medical Materials - Fan, Daoyang; Li, Yan; Wang, Xing; Zhu, Tengjiao; Wang, Qi; Cai, Hong; Li, Weishi; Tian, Yun; Liu, Zhongjun (Frontiers in Pharmacology, 2020)
Three-dimensional (3D) printing enables patient-specific anatomical level productions with high adjustability and resolution in microstructures. With cost-effective manufacturing for high productivity, 3D printing has become a leading healthcare and pharmaceutical manufacturing technology, which is suitable for variety of applications including tissue engineering models, anatomical models, pharmacological design and validation model, medical apparatus and instruments. Today, 3D printing is offering clinical available medical products and platforms suitable for emerging research fields, including tissue and organ printing. In this review, our goal is to discuss progressive 3D printing technology and its application in medical materials. The additive overview also provides manufacturing techniques and printable materials.